A manganese-carbon composite catalyst for room temperature catalytic oxidation of toluene, a preparation method and application thereof

CN122974307APending Publication Date: 2026-10-27ZHENGZHOU TOBACCO RES INST OF CNTC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611006460.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0008]本发明的第一个目的是提供一种用于室温甲苯催化氧化的锰碳复合催化剂,以解决常规锰碳复合催化剂的室温甲苯催化氧化性能有待提升的问题

Benefits of technology

[0008]本发明的第一个目的是提供一种用于室温甲苯催化氧化的锰碳复合催化剂,以解决常规锰碳复合催化剂的室温甲苯催化氧化性能有待提升的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122974307A_ABST
    Figure CN122974307A_ABST
Patent Text Reader

Abstract

The application belongs to the field of catalytic treatment of volatile organic compounds (VOCs), and particularly relates to a manganese-carbon composite catalyst for catalytic oxidation of toluene at room temperature, a preparation method and application thereof. The manganese-carbon composite catalyst is an interface contact composite structure formed by a manganese oxide catalytic active component and carbon, the mass ratio of the manganese oxide catalytic active component is 40-70%, the main crystal phase of the manganese oxide catalytic active component is beta-MnO2; the content of low-valence Mn accounts for 0.68-0.71 of the total Mn content, the average oxidation state of Mn is 2.26-2.43, and the ratio of surface adsorption oxygen to lattice oxygen is 4.67-7.30; the I D / I G of the carbon material is 1.14-1.23. Through multiple action mechanisms such as manganese valence state regulation, oxygen vacancy activation, carbon defect synergy and interface electronic coupling, the manganese-carbon composite catalyst effectively plays the adsorption-catalysis synergy, and performs excellently in catalytic oxidation removal of toluene at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic treatment of volatile organic compounds (VOCs), specifically relating to a manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature, its preparation method, and its application. Background Technology

[0002] Toluene, a typical volatile organic compound (VOC), is a major component of indoor air pollution and industrial waste gas. Long-term exposure to toluene-containing environments can damage the human nervous system, respiratory system, and liver. Toluene is also a significant precursor to photochemical smog and ozone formation. Therefore, developing efficient and low-cost toluene removal technologies has significant environmental and social value.

[0003] Catalytic oxidation is one of the effective methods for treating toluene, and its core lies in developing efficient and stable catalysts. An ideal catalyst should possess the following characteristics: 1) It should be able to achieve efficient oxidation at room temperature or lower temperatures to reduce energy consumption; 2) It should have good deep oxidation capabilities, completely mineralizing toluene into CO2 and H2O, avoiding the formation of toxic intermediate products; 3) It should have excellent stability, being able to operate for a long time without deactivation; 4) It should have widely available raw materials, simple preparation processes, and low costs.

[0004] Carbon materials (such as graphite, activated carbon, and biochar) possess high specific surface area and excellent adsorption capacity, enabling them to effectively enrich toluene molecules at room temperature. Transition metal oxides (such as manganese oxides, cobalt oxides, and iron oxides) exhibit good redox properties and can provide catalytic active sites. Combining these two materials is expected to achieve adsorption-catalysis synergy and improve the room temperature toluene oxidation efficiency. Among them, manganese oxides are particularly valuable due to their high natural abundance, environmental friendliness, low toxicity, and diverse valence states (Mn). 2+ / Mn 3+ / Mn 4 + Its advantages, such as [missing information], make it an ideal active component for constructing composite catalysts.

[0005] In the prior art, there are reports of combining manganese dioxide and biochar through ball milling. For example, Chinese invention patent application CN117101645A, published on November 24, 2023, discloses a method for preparing manganese dioxide / biochar composite catalyst by mechanochemical method. It uses a hydrothermal method to pre-synthesize α-MnO2 with a micro-nano hierarchical structure, pyrolyzes biomass at a high temperature of 800-1100℃ to prepare biochar, and then combines the two by ball milling. However, this technology has the following limitations: 1) The manganese dioxide used needs to be synthesized in two steps: hydrothermal method (reaction at 120℃ for 10-12 hours) and high-temperature calcination (pyrolysis at 500℃ for 120 minutes). Biochar needs to be prepared by pyrolysis at a high temperature of 800-1100℃. The process is complicated, energy-intensive, and time-consuming; 2) This composite material is mainly used to activate persulfate to degrade organic pollutants in water, and its application in gas-phase toluene catalytic oxidation is not involved; 3) This technology only gives a general range of ball milling parameters and does not reveal the intrinsic relationship between ball milling parameters and material microstructure (such as manganese valence distribution, oxygen vacancy concentration, and carbon defect density); 4) This technology does not involve the performance of the material in catalytic oxidation of toluene at room temperature, and it is impossible to determine whether it is suitable for room temperature toluene removal scenarios.

[0006] Chinese invention patent application CN 116832805 A, published on October 3, 2023, discloses a graphite-supported manganese dioxide catalyst from waste lithium-ion batteries, its preparation method, and its application. The method involves wet ball milling waste graphite powder, dispersing the resulting activated graphite in a mixed solution of KMnO4 and MnSO4, and subjecting the reaction to a hydrothermal reaction at 120–180°C for 8–20 hours to obtain the graphite-supported manganese dioxide catalyst from waste lithium-ion batteries. This catalyst utilizes non-metallic and metallic dopants contained in the graphite from waste lithium-ion batteries to provide defect sites for anchoring manganese dioxide, thereby generating highly dispersed and enhanced active manganese dioxide sites to improve formaldehyde catalytic performance. Simultaneously, the formation of manganese dioxide promotes graphite exfoliation, further expanding the surface area of ​​the graphite from waste lithium-ion batteries, which in turn affects the final morphology of the manganese dioxide growth, significantly increasing the active area and thus enhancing the formaldehyde catalytic activity.

[0007] The above method relies on wet ball milling of waste graphite and in-situ hydrothermal synthesis of manganese dioxide. Different properties of waste graphite may have an uncontrollable impact on the catalytic performance of the catalyst. At the same time, the preparation process is relatively complex and generates a large amount of wastewater. The experimental results show that the formaldehyde removal rate is 80%~97% within 1 hour, and there is still room for further improvement in the overall catalytic oxidation efficiency. Summary of the Invention

[0008] The first objective of this invention is to provide a manganese-carbon composite catalyst for the room-temperature catalytic oxidation of toluene, in order to address the problem that the room-temperature catalytic oxidation performance of conventional manganese-carbon composite catalysts for toluene needs to be improved.

[0009] The second objective of this invention is to provide a method for preparing the above-mentioned manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature, so as to solve the problems of complex preparation processes and large amounts of wastewater generated by existing manganese-carbon composite catalysts.

[0010] The third objective of this invention is to provide the application of the above-mentioned manganese-carbon composite catalyst in the catalytic oxidation removal of toluene, thereby solving the problem of poor catalytic oxidation removal capacity of existing catalysts for toluene.

[0011] To achieve the first objective mentioned above, the technical solution adopted by this invention is as follows: A manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature is disclosed. It comprises an interfacial composite structure of manganese oxide catalytic active component and carbon. The manganese oxide catalytic active component accounts for 40-70% by mass, and its main crystalline phase is β-MnO2. Low-valence Mn accounts for 0.68-0.71% of the total Mn content, the average oxidation state of manganese is 2.26-2.43, and the ratio of adsorbed oxygen to lattice oxygen is 4.67-7.30. The carbon material contains I... D / I G The value is 1.14~1.23; the low valence state Mn is Mn 2+ and Mn 3+ .

[0012] This invention is an improved invention. Through multiple mechanisms such as manganese valence state regulation, oxygen vacancy activation, carbon defect synergy, and interfacial electronic coupling, it effectively exerts the adsorption-catalytic synergy of manganese-carbon composite catalysts, and performs excellently in the catalytic oxidation removal of toluene at room temperature.

[0013] Experimental results show that this catalyst can achieve a toluene removal rate of over 99% and a CO2 yield of ≥53% at room temperature, demonstrating excellent toluene removal capabilities. Furthermore, long-term stability experiments show that the fixed-bed reactor based on this catalyst has achieved stable operation for over 7 days, indicating good structural stability of the catalyst and its ability to operate long-term without deactivation.

[0014] Preferably, the low-valence state Mn accounts for 0.70~0.71% of the total Mn content, the average oxidation state of manganese is 2.26~2.31, and the ratio of surface adsorbed oxygen to lattice oxygen is 6.27~7.30; the carbon material I D / I G The value is 1.21~1.23. Under the above-mentioned preferred control parameters, the catalytic oxidation removal capacity of p-toluene reaches about 99.1%~99.4%, which is suitable for the efficient removal of p-toluene.

[0015] Preferably, the BET specific surface area of ​​the manganese-carbon composite catalyst is 23-46 m². 2 / g, pore volume 0.028~0.037 cm³ 3 / g. Under the above-mentioned control parameters, it is shown that manganese oxide and carbon materials achieve close interfacial contact and composite, which is beneficial to improving the catalytic oxidation activity of the catalyst through the interfacial electronic coupling mechanism.

[0016] More preferably, the BET specific surface area of ​​the manganese-carbon composite catalyst is 23-32 m². 2 / g, pore volume 0.028~0.031 cm³ 3 / g. Under the above-mentioned optimized BET specific surface area and pore volume parameters, the catalytic oxidation removal capacity for toluene reaches the best level.

[0017] To achieve the second objective mentioned above, the technical solution adopted by the present invention is as follows: The above-mentioned method for preparing the manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature involves performing a full solid-phase high-energy ball milling of β-MnO2 and carbon materials; β-MnO2 accounts for 40-70% of the total mass of β-MnO2 and carbon materials.

[0018] The present invention discloses a method for preparing a manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature. This method utilizes commercially available raw materials and is prepared via a solid-phase ball milling process. It is solvent-free and requires no high-temperature hydrothermal / calcination steps. The room-temperature catalytic oxidation material is specifically designed for the removal of gaseous toluene. Furthermore, this method generates no wastewater throughout the entire process, making it environmentally friendly. The simple process effectively reduces the industrial production cost of the catalyst, making it suitable for large-scale application.

[0019] Preferably, the ball-to-material ratio of the high-energy ball mill is 100-120:1, the rotation speed is 700-900 rpm, and the effective ball milling time is 5 hours or more. The effective ball milling time refers to the time the ball mill is in the grinding state, excluding the settling time. The effective ball milling time is further preferably controlled within 5-8 hours.

[0020] More preferably, the high-energy ball mill adopts a forward / reverse rotation switching mode, switching between forward and reverse rotation every 15-20 minutes, with a rest period of 2-5 minutes in between. One forward / reverse rotation constitutes one cycle, and the number of cycles is 10-16. This forward / reverse rotation switching mode achieves high ball milling efficiency without damaging the material structure.

[0021] Preferably, the high-energy ball milling is carried out in a grinding jar made of zirconia, and the grinding balls are made of zirconia with a diameter of 12-15 mm. Using a grinding jar and grinding balls made of zirconia results in high grinding efficiency and prevents contamination of the material during the grinding process.

[0022] To achieve the third objective mentioned above, the technical solution adopted by this invention is as follows: The above-mentioned manganese-carbon composite catalyst is used in the catalytic oxidation removal of toluene.

[0023] The manganese-carbon composite catalyst of the present invention exhibits excellent room-temperature toluene catalytic oxidation activity when catalytically oxidizing and removing toluene. Its performance is superior to that of simple physical mixtures and simple grinding mixtures. This proves that the tightly bound interface and novel chemical state constructed by high-energy ball milling are the key to forming a highly efficient adsorption-catalytic synergistic reaction center, and are also the intrinsic reason why the manganese-carbon composite catalyst exhibits excellent toluene removal ability.

[0024] Preferably, the catalytic oxidation is carried out in a fixed-bed reactor at room temperature. Achieving the catalytic oxidation removal of toluene through a room-temperature fixed-bed reaction offers strong industrial adaptability, stable catalytic oxidation removal performance, and facilitates centralized and efficient treatment of industrial gases. Attached Figure Description

[0025] Figure 1 SEM images of C@MnO2-x (x=8, 10, 12, 14 and 16) in this invention: (a) C@MnO2-8; (b) C@MnO2-10; (c) C@MnO2-12; (d) C@MnO2-14; (e) C@MnO2-16; (f) original carbon material; (g) original MnO2; Figure 2 The XRD patterns of the C@MnO2-x (x=8, 10, 12, 14, 16) composite materials of Examples 1-5 of the present invention are shown. Figure 3 Raman spectra of C@MnO2-x (x=8, 10, 12, 14, 16) in Examples 1-5 of the present invention; Figure 4 XPS spectra of C@MnO2-x (x=8, 10, 12, 14, 16) in Examples 1-5 of the present invention: (a) Mn 2p; (b) Mn 3s and (c) O 1s; Figure 5 The results of toluene removal capacity tests of C@MnO2-x (x=8, 10, 12, 14, 16) in Examples 1-5 of this invention are shown. Figure 6 This is a long-term experiment on the removal of toluene by C@MnO2-16 in Example 5 of the present invention. Detailed Implementation

[0026] (I) Preferred embodiments of the manganese-carbon composite catalyst for room temperature toluene catalytic oxidation of the present invention, its preparation method and application Given that the synthesis of existing manganese-carbon composite catalysts is characterized by cumbersome processes, high energy consumption, long cycles, and unsuitability for industrial applications, this invention proposes a manganese-carbon composite catalyst with well-defined structural features, a simple preparation process, and the ability to efficiently catalyze the oxidation of toluene at room temperature. Through the combined effects of multiple mechanisms, including adsorption-catalysis synergy, manganese valence state regulation, oxygen vacancy activation, carbon defect synergy, interfacial electronic coupling, and crystal phase synergy, the catalytic oxidation activity of the manganese-carbon composite catalyst is improved.

[0027] Specifically, the manganese-carbon composite catalyst of the present invention is an interfacial contact composite structure formed by manganese oxide catalytic active component and carbon. The mass proportion of the manganese oxide catalytic active component is 40-70%, and the main crystalline phase of the manganese oxide catalytic active component is β-MnO2. The low-valence state Mn accounts for 0.68-0.71% of the total Mn content, the average oxidation state of manganese is 2.26-2.43, and the ratio of surface adsorbed oxygen to lattice oxygen is 4.67-7.30. The carbon material I D / I G The value is 1.14~1.23.

[0028] The preferred mass percentage of the catalytically active component, manganese oxide, is 50±5%.

[0029] The room-temperature toluene catalytic oxidation performance of the above-mentioned manganese-carbon composite catalyst is based on the following synergistic mechanism: (I) Adsorption-catalysis synergistic mechanism The carbon material in the catalyst possesses abundant π-π conjugated structures and a large specific surface area, enabling it to effectively adsorb and enrich toluene molecules at room temperature through van der Waals forces and π-π interactions, thereby increasing the local concentration of toluene on the catalyst surface. Simultaneously, the manganese oxide (β-MnO2) in the catalyst provides catalytic active centers, activating molecular oxygen through redox cycles on its surface, thus oxidizing and decomposing the adsorbed toluene. This adsorption-catalysis synergy overcomes the limitation of separation between adsorption sites and active sites in traditional catalysts, achieving rapid enrichment and efficient oxidation of toluene molecules.

[0030] (II) Manganese price regulation mechanism The valence state distribution of Mn in manganese oxides is a key factor determining catalytic activity. In the catalyst of this invention, manganese is present primarily as Mn. 2+ Mn 3+ Mn 4+ Three valence states coexist, among which the low valence state manganese (Mn) 2+ +Mn 3+ The proportion of manganese in the total manganese is 0.68~0.71%, and the average oxidation state (AOS) of manganese is 2.26~2.43. The presence of low-valence manganese has the following effects: 1) Mn 3+1) Possessing unpaired electrons, it can act as a Lewis acid site to adsorb π electrons from toluene molecules, promoting the activation of CH bonds; 2) Low-valence manganese is closely related to oxygen vacancies, Mn 3+ The presence of Mn facilitates the extraction of lattice oxygen, forming oxygen vacancy defects; 3) Mn 2+ / Mn 3+ / Mn 4+ The reversible redox cycle between Mn 4+ + e - Mn 3+ Mn 3+ + e - Mn 2+ This provides a continuous electron transfer pathway for the oxidation of toluene.

[0031] (III) Oxygen Vacancy Activation Mechanism High proportion of surface-adsorbed oxygen (O) in the catalyst ads / O latt The range of oxygen vacancies (4.67~7.30) indicates the presence of abundant oxygen vacancies on the surface. The role of oxygen vacancies in the catalytic oxidation of toluene is manifested in the following ways: 1) The presence of oxygen vacancies lowers the migration energy barrier of lattice oxygen, enabling bulk lattice oxygen to migrate rapidly to the surface to participate in the reaction. At the same time, surface oxygen vacancies can also replenish oxygen from the bulk phase, achieving a continuous supply of oxygen species; 2) As active sites, oxygen vacancies can lower the activation energy barrier of key steps in the toluene oxidation reaction (such as CH bond breaking and aromatic ring opening).

[0032] (iv) Cooperative mechanism of carbon defects High-density defects (I) in carbon materials in catalysts D / I G The contributions of carbon defect sites (1.14~1.23) to catalytic performance include: 1) Carbon defect sites (such as edge sites, vacancies, and dangling bonds) have high surface energy, which can enhance the adsorption strength of toluene molecules; 2) Carbon defects can regulate the electronic structure of carbon materials, promote the transfer of electrons from carbon materials to manganese oxides, and improve the redox activity of manganese; 3) Carbon defect sites can serve as anchoring points for manganese oxide nanoparticles, enhance the interfacial bonding strength between manganese oxides and carbon materials, and prevent the aggregation and loss of active components.

[0033] (v) Interface electronic coupling mechanism The tight interfacial contact created by mechanical ball milling fosters a strong electronic coupling effect between the carbon material and manganese oxide. The carbon material, acting as an electron donor, can transfer electrons to the manganese oxide, promoting Mn... 4+ Restored to Mn 3+ or Mn 2+This increases the proportion of low-valence manganese and the concentration of oxygen vacancies. Simultaneously, the electron redistribution at the interface alters the band structure of manganese oxides, optimizing their activation ability for molecular oxygen.

[0034] (vi) Crystal phase coordination mechanism This invention prepares a manganese-carbon composite catalyst via a one-step ball milling method. The one-step ball milling process does not change the main crystal form of manganese dioxide, and only achieves effective interfacial coupling between carbon materials and manganese oxides through mechanical force, thus achieving excellent room temperature toluene catalytic oxidation performance.

[0035] The above-mentioned manganese-carbon composite catalyst is prepared by directly ball-milling and mixing commercially available β-MnO2 and commercially available carbon materials. The structure of the catalyst is regulated by controlling the ball-milling parameters. The average particle size of the commercially available β-MnO2 can be 8~15μm; in the examples below, it was purchased from Zhongkexin Science and Technology (Hubei) Co., Ltd., with an average particle size of 12μm. The commercially available carbon material is preferably activated carbon. For example, activated carbon used as an adsorbent material in air purifiers; this type of activated carbon material is a conventional adsorbent consumable. The average particle size can be 5~10μm. D / I G =1.0~1.1. In the following examples, the commercially available carbon materials are all activated carbon with an average particle size of 8 μm.

[0036] If the ball milling is insufficient, the removal capacity of toluene will not be significantly improved; if the ball milling is excessive, it will significantly increase the ball milling cost, which is not conducive to improving the economic efficiency of industrial production.

[0037] The ball mill preferably adopts a forward and reverse rotation switching mode, switching between forward and reverse rotation every 15 to 20 minutes, with a resting time of 2 to 5 minutes in between. One forward and reverse rotation is one cycle, and the number of cycles is 10 to 16.

[0038] The ball-to-material ratio for ball milling is 100~120:1, the rotation speed is 700~900 rpm, and the effective ball milling time is more than 5 hours. Ball milling is carried out in a grinding jar made of zirconia, and the grinding balls are made of zirconia with a diameter of 12~15 mm.

[0039] When using the above-mentioned manganese-carbon composite catalyst to remove toluene, a conventional fixed-bed reactor can be used, with the gas flow rate controlled at 500-600 mL / min, the toluene concentration at 100-150 ppm, and the gas hourly space velocity (GHSV) at 750,000-800,000 h⁻¹. -1 .

[0040] The preferred embodiments described above will be illustrated below with specific examples.

[0041] Examples 1-5 The preparation method of the manganese-carbon composite catalyst for the room-temperature catalytic oxidation of toluene in Examples 1-5 is described in detail below: Zirconia balls with a diameter of 15 mm, 1 g of commercial β-MnO2, and 1 g of commercial carbon material were placed in a zirconia grinding jar, maintaining a ball-to-material ratio of 100:1. The grinding jar was then placed in a planetary ball mill, with the rotation speed set to 700 rpm. The ball milling process employed an alternating forward and reverse rotation mode, switching between forward and reverse rotation every 15 minutes, with a 2-minute rest period in between; a complete forward and reverse rotation cycle took 34 minutes. By setting different numbers of cycles, a series of C@MnO2-x samples were obtained, where x represents the number of ball milling cycles, which were 8, 10, 12, 14, and 16 (corresponding to Examples 1-5, respectively).

[0042] The manganese-carbon composite catalysts for the catalytic oxidation of toluene at room temperature described in Examples 1-5 have an interfacial contact composite structure formed by the manganese oxide catalytic active component and carbon. The manganese oxide catalytic active component accounts for 50% by mass, and its main crystalline phase is β-MnO2. Specific structural characteristics are described below: Interface combined with structure: Figure 1 ae represents SEM images of C@MnO2-x (x=8, 10, 12, 14, and 16). Figure 1 f and 1g are SEM images of the carbon material and MnO2. The images show that both pure carbon and pure MnO2 exhibit a blocky structure; however, after ball milling, the C@MnO2-x series samples prepared with different cycles all show a composite morphology of carbon material and MnO2, with a relatively tight interface between the two phases. This composite structure is beneficial for enhancing interfacial interactions, thus providing a good structural basis for the catalytic oxidation of toluene.

[0043] Crystal structure: such as Figure 2 As shown, for the C@MnO2-x series samples, a (002) diffraction peak of graphite appeared near 26.52°, while characteristic diffraction peaks at 28.72°, 37.83°, and 56.72° can be attributed to the (110), (101), and (211) crystal planes of β-MnO2. The results indicate that the main phase of this series of samples is β-MnO2, and the ball milling process did not change the main crystal structure of manganese dioxide; the effective composite between carbon materials and manganese oxides was achieved only through mechanical force.

[0044] Specific surface area and pore volume: As shown in Table 1, as the number of cycles increased from 8 to 16, the specific surface area of ​​the material increased from 52.3 m² / s². 2 / g gradually decreased to 23.9 m 2 / g, while the pore volume increased from 0.038 cm³. 3 / g decreased to 0.028 cm3 / g. This result indicates that during the one-step ball milling process, MnO2 and carbon materials can achieve relatively complete composite under mechanical action, with MnO2 gradually dispersing and adhering to the surface and pores of the carbon material. With increasing cycle number, more MnO2 covers or occupies the original adsorption sites of the carbon material, thereby reducing the effective pores accessible to N2 molecules, leading to a decrease in the specific surface area and pore volume of the material.

[0045] Table 1 Structural parameters of C@MnO2-x Carbon defect structure: I of original carbon materials D / I G =1.00, as Figure 3 As shown, when the number of iterations is 8, 10, 12, 14, and 16, the corresponding I... D / I G The values ​​are 1.14, 1.14, 1.15, 1.21 and 1.23 respectively, showing an overall trend of gradually increasing with the number of cycles.

[0046] Surface chemical state: Figure 4 a presents the XPS spectra of Mn 2p. It can be observed that all C@MnO2-x series samples exhibit the same Mn 2p... 3 / 2 and Mn 2p 1 / 2 The regions all exhibit a distinct asymmetric broad peak characteristic, indicating that Mn species on the catalyst surface exist in a multivalent coexisting form. Regarding Mn 2p... 3 / 2 Peak fitting analysis revealed that the peaks with binding energies at approximately 641.0 eV, 642.3 eV, and 643.6 eV belong to Mn. 2+ Mn 3+ and Mn 4+ Species.

[0047] Table 2 shows that in the C@MnO2-x series constructed by one-step ball milling, as the number of ball milling cycles increases from 8 to 16, (Mn 2+ +Mn 3+ The ratio of Mn to total Mn increased from 0.66 to 0.71.

[0048] The oxidation state of Mn on the surface of the MnO2 catalyst was analyzed by Mn 3s, such as... Figure 4As shown in b, the binding energy differences between the two Mn3s peaks for different catalysts are as follows: C@MnO2-8 (5.75 eV), C@MnO2-10 (5.80 eV), C@MnO2-12 (5.81 eV), C@MnO2-14 (5.90 eV), and C@MnO2-16 (5.95 eV). The corresponding AOS values ​​of Mn (calculated as AOS = 8.956 - 1.126ΔE3s, where ΔE3s is the Mn 3s energy level splitting) are 2.48, 2.43, 2.41, 2.31, and 2.26, respectively. C@MnO2-16 has the lowest AOS value, suggesting that its surface may contain more Mn. 3+ It has more surface defects. This indicates that extending the ball milling time can promote the surface Mn content. 4+ Towards lower valence state Mn 2+ and Mn 3+ The transformation reduces the average oxidation state of Mn. This phenomenon can be attributed to lattice distortion and oxygen vacancy formation induced by high-energy mechanical forces. During ball milling, the Mn-O bonds break and rearrange under repeated impact and shearing, and some lattice oxygen is released to form oxygen vacancies. To maintain charge balance, neighboring Mn... 4+ Tends to be reduced to Mn 3+ or Mn 2+ This leads to a decrease in the AOS value. Therefore, a decrease in the AOS value can serve as an important electronic structure characterization indicator of increased oxygen vacancies in materials.

[0049] Figure 4 c shows the high-resolution O 1s spectra of the series of samples. The O 1s spectra of all samples can be fitted to three characteristic peaks, with binding energies located at approximately 529.9 eV, 531.6 eV, and 532.9 eV, respectively, corresponding to lattice oxygen (O₂). latt ), surface adsorbed oxygen (O) ads ) and surface hydroxyl oxygen (O OH ).

[0050] Table 2 shows that different preparation processes significantly affected the distribution of oxygen species on the sample surface. For the C@MnO2-x series samples prepared by one-step ball milling, as the number of ball milling cycles increased from 8 to 16, the O2 content decreased. ads / O latt The ratio showed a significant upward trend, increasing from 3.94 for C@MnO2-8 to 7.30 for C@MnO2-16. This change indicates that extending the ball milling time can effectively disrupt the crystal structure of MnO2, introducing more oxygen vacancies on the catalyst surface, thereby significantly increasing the proportion of surface-adsorbed oxygen species.

[0051] Table 2 Chemical states of Mn and O in C@MnO2-x The application of the manganese-carbon composite catalysts in the catalytic oxidation removal of toluene in Examples 1-5 is described in detail below: The performance evaluation of C@MnO2-x for toluene removal was conducted in a fixed-bed reactor. At 25°C, 40 mg of catalyst was loaded into a quartz reactor tube, and toluene standard gas carried by nitrogen was introduced at a flow rate of 500 mL / min. The initial toluene concentration was 100 ppm, and the gas hourly space velocity (GHSV) was 750,000 h⁻¹. -1 A handheld portable VOC detector was used to measure and record the toluene concentration at the inlet and outlet in real time. A multi-analyzer was used to measure and record the carbon dioxide and carbon monoxide concentrations at the outlet.

[0052] Toluene removal rate (%) is calculated using the following formula: Among them, C in (ppm) and C out (ppm) represents the concentration of toluene in the inlet gas and the outlet gas, respectively.

[0053] Carbon dioxide production (%) is calculated using the following formula: Carbon monoxide production (%) is calculated using the following formula: C CO2 (ppm) and C CO (ppm) indicates the concentration of carbon dioxide and carbon monoxide in the outlet gas, while C in This represents the concentration of toluene in the inlet gas.

[0054] Figure 5 The results show the toluene removal capacity of the C@MnO2-x series materials at room temperature. At cycle numbers of 8, 10, 12, 14, and 16, the corresponding removal rates were 62.3%, 95.3%, 97.6%, 99.1%, and 99.4%, respectively, showing a significant increase with increasing cycle number. Analysis of the reaction products revealed no CO, only CO2, with yields of 19.6%, 46.2%, 47.9%, 53.1%, and 53.5%, respectively. C@MnO2-16 exhibited the highest removal rate and CO2 yield, indicating that this sample demonstrates the best toluene removal capacity in this series.

[0055] (ii) Comparative Example Comparative Example 1: Physical Mixing In this comparative example, a manganese-carbon composite material was prepared by simply mixing 1 g of β-MnO2 and 1 g of carbon in a mortar, denoted as C+MnO2. Characterization revealed that carbon and MnO2 largely retained their original morphologies, coexisting primarily in a simple packing manner with no obvious interfacial recombination; no new phase formation was observed. D / I G =1.05, significantly lower than the ball-milled sample. The removal rate of toluene by carbon material alone was 38.7%, the removal rate of toluene by β-MnO2 alone was 26.1%, and the removal rate of toluene by the physically mixed sample (C+MnO2) was 47.5%, which was significantly lower than the ball-milled composite sample.

[0056] Therefore, simple physical mixing cannot create tight interfacial contact and effective structural control, thus failing to achieve efficient synergy between adsorption and catalysis.

[0057] Comparative Example 2: Simple Grinding In this comparative example, the manganese-carbon composite material was prepared by manually grinding 1 g of β-MnO2 and 1 g of carbon in a mortar for 30 minutes, denoted as C / MnO2. Characterization revealed that although the microstructure changed somewhat, the overall structure remained similar to the original material, and the interaction between the two phases was relatively limited; no new phase formation was observed. D / I G =1.12, slightly higher than the physically mixed sample, but significantly lower than the ball-milled sample. The simple grinding sample (C / MnO2) had a toluene removal rate of 56.6%, which was slightly better than the physically mixed sample, but still significantly lower than the ball-milled composite sample.

[0058] Therefore, low-intensity grinding is insufficient to induce significant phase changes and structural defects, and cannot construct efficient adsorption-catalysis synergistic reaction centers.

[0059] (III) Stability Test of Experimental Examples The C@MnO2-16 prepared in Example 5 was continuously run in a fixed-bed reactor for 7 days. The same material was used for cyclic testing: after each reaction period, the valve was switched, and the VOC detector reading returned to a stable value before the experiment began, ensuring that all experimental cycles were started under the same initial conditions. Then, the valve was switched again to allow toluene gas to pass through the material. This process was repeated multiple times, and the results are as follows: Figure 6 As shown.

[0060] Figure 6The results showed that during 7 days of continuous testing, the toluene removal rate remained stable between 98.9% and 99.6%, with no significant decrease. Characterization of the reacted material (C@MnO2-16-AR) revealed that the morphology was not significantly different from that before the reaction, and no significant agglomeration or structural collapse was observed; the crystal phase did not change significantly compared to before the reaction, and no new impurity phases were detected; Mn 2+ Mn 3 + Mn 4+ Three oxidation states coexist, and ΔE = 5.28 eV, so AOS = 2.40 (2.26 before the reaction); O ads / O latt =7.14 (7.30 before reaction); (Mn) 2+ +Mn 3+ The Mn / total Mn ratio decreased from 0.71 to 0.68; this relatively small change indicates that the surface electronic structure remains relatively stable during the reaction. In summary, the catalyst of this invention exhibits excellent stability and can operate stably for extended periods.

[0061] In summary, the manganese-carbon composite catalyst of the present invention has the following outstanding features: 1. Under room temperature conditions, the removal rate of toluene can reach over 99%, the CO2 yield can reach over 53%, and CO was not detected in the reaction products, indicating that it has excellent deep oxidation ability and avoids the generation of toxic intermediate products.

[0062] 2. Compared with single-component (carbon material removal rate 38.7%, β-MnO2 removal rate 26.1%), physically mixed sample (C+MnO2 removal rate 47.5%), and simply ground sample (C / MnO2 removal rate 56.6%), the toluene removal rate of the catalyst of this invention is improved to over 99%, indicating that the tight interfacial structure constructed by ball milling achieves efficient synergy between adsorption and catalysis.

[0063] 3. Continuous cyclic testing over 7 days showed that the catalyst maintained a stable toluene removal rate between 98.9% and 99.6%, with no significant degradation. The morphology, crystal phase, and surface electronic structure of the material remained stable after the reaction.

[0064] 4. Using commercially available β-MnO2 and carbon materials as raw materials, there is no need for complex hydrothermal synthesis and high-temperature pyrolysis steps. The raw materials are readily available and the cost is low.

[0065] 5. It is prepared by a one-step mechanical ball milling method, without the participation of solvents, and without the emission of wastewater and exhaust gas, which is in line with the concepts of green chemistry and sustainable development.

[0066] 6. By adjusting the number of ball milling cycles, the microstructure parameters of the catalyst can be systematically changed (Ic). D / I GFrom 1.14 to 1.23, AOS decreased from 2.48 to 2.26, O ads / O latt (From 3.94 to 7.30), toluene removal rate increased from 62.3% to 99.4%, and CO2 yield increased from 19.6% to 53.5%, establishing a clear structure-performance relationship.

[0067] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature, characterized in that, It is an interfacial composite structure formed by manganese oxide catalytic active component and carbon. The mass proportion of manganese oxide catalytic active component is 40-70%, and the main crystalline phase of manganese oxide catalytic active component is β-MnO2. The low-valence state Mn accounts for 0.68-0.71% of the total Mn content, the average oxidation state of manganese is 2.26-2.43, and the ratio of surface adsorbed oxygen to lattice oxygen is 4.67-7.

30. The carbon material I D / I G The value is 1.14~1.23; the low valence state Mn is Mn 2+ and Mn 3+ .

2. The manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature as described in claim 1, characterized in that, The low-valence state Mn accounts for 0.70~0.71% of the total Mn content, the average oxidation state of manganese is 2.26~2.31, and the ratio of adsorbed oxygen on the surface to lattice oxygen is 6.27~7.30; the I of carbon materials D / I G It is 1.21~1.

23.

3. The manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature as described in claim 1 or 2, characterized in that, The BET specific surface area of ​​the manganese-carbon composite catalyst is 23-46 m². 2 / g, pore volume 0.028~0.037 cm³ 3 / g.

4. The manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature as described in claim 3, characterized in that, The BET specific surface area of ​​the manganese-carbon composite catalyst is 23-32 m². 2 / g, pore volume 0.028~0.031 cm³ 3 / g.

5. A method for preparing a manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature, characterized in that, β-MnO2 and carbon materials were subjected to all-solid-phase high-energy ball milling; β-MnO2 accounted for 40-70% of the total mass of β-MnO2 and carbon materials.

6. The method for preparing the manganese-carbon composite catalyst for the room-temperature catalytic oxidation of toluene as described in claim 5, characterized in that, The high-energy ball mill has a ball-to-material ratio of 100~120:1, a rotation speed of 700~900 rpm, and an effective ball milling time of more than 5 hours.

7. The method for preparing the manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature as described in claim 6, characterized in that, The high-energy ball mill adopts a forward and reverse rotation switching mode, switching between forward and reverse rotation every 15 to 20 minutes, with a resting time of 2 to 5 minutes in between. One forward and reverse rotation is considered one cycle, and the number of cycles is 10 to 16.

8. The method for preparing the manganese-carbon composite catalyst for the catalytic oxidation of toluene at room temperature as described in claim 5, characterized in that, The high-energy ball milling is carried out in a grinding jar made of zirconia, and the grinding balls are made of zirconia with a diameter of 12~15mm.

9. The application of a manganese-carbon composite catalyst as described in any one of claims 1 to 4 in the catalytic oxidation removal of toluene.

10. The application as described in claim 9, characterized in that, The catalytic oxidation is carried out in a fixed-bed reactor at room temperature.

Citation Information

Patent Citations

  • Waste lithium battery graphite loaded manganese dioxide catalyst as well as preparation method and application thereof

    CN116832805A

  • Method for preparing manganese dioxide / biochar composite catalyst by mechanochemical method

    CN117101645A